How ChatGPT transformed teachers: the role of basic psychological needs in enhancing digital competence - Zhou, Jinshan; Shen, Lihan; Chen, Weibang (Frontiers in Psychology, 2024)
Introduction With the rapid development of ChatGPT, its application in the field of education has garnered widespread attention. This study aims to explore the impact of ChatGPT on teachers’ digital competence (TDC) and the mediating role of basic psychological needs satisfaction (BPNS). Methods The study was conducted in China, collecting questionnaire data from 632 teachers through the QuestionStar platform. Structural equation modeling was employed using SmartPLS 4.0 to examine the effects of ChatGPT usage on TDC and its relationship with BPNS. Results The findings indicate that ChatGPT has a significant effect on TDC, primarily through the fulfillment of competence and relatedness needs, while the impact of autonomy on TDC was not significant. Discussion The results indicate that ChatGPT can enhance TDC and improve intrinsic motivation by satisfying their basic psychological needs. It is recommended that the design of educational tools consider teachers’ psychological needs to promote their professional development and well-being. This provides practical guidance for educational institutions, emphasizing the importance of teachers in the digital transformation process.